THE IMPLEMENTATION OF INQUIRY LEARNING MODEL TO IMPROVE CRITICAL THINKING SKILLS OF 4TH SURABAYA SENIOR HIGH SCHOOL’S STUDENTS IN PHYSICS MATERIAL STATIC FLUID - WIBIANE, AGISTA; ARIFIN IMAM SUPARDI, ZAINUL (Inovasi Pendidikan Fisika, 2020)
Abstract This research aims to determine the improvement of students critical thinking skills towards the implementation of physics learning with inquiry models in fluid physics material. This type of research is descriptive-quantitative with pre-experimental design and one group pre-test post-test design. The subjects of this study were students of class XI in academic year 2019/2020 at SMAN 4 Surabaya. The instruments which has been used to collect data were essays test, observation, and questionnaire. Based on the data analysis, the results of improvement students critical thinking skills increased significantly and consistently with more than 50% of the students in all three classes in n-gain high category. The implementation of inquiry learning in all three classes obtained a very good grade in average mode and students responses to the learning model are in good category in all three classes. This is prove that the inquiry model is very effective to be used to improve students critical thinking skills on static fluid physics material. Keywords: Inquiry Learning Models and Critical Thinking Skills